Hypoxia-induced epigenetic regulation of miR-485-3p promotes stemness and chemoresistance in pancreatic ductal adenocarcinoma via SLC7A11-mediated ferroptosis - Xinxin Liu; Zhihua Huang; Qiuzheng Chen; Kai Chen; Weikang Liu; Guangnian Liu; Xiangyu Chu; Dongqi Li; Yongsu Ma; Xiaodong Tian; Yinmo Yang (Cell Death Discovery, 2024)
Abstract The mechanism of hypoxia in chemoresistance of pancreatic ductal adenocarcinoma (PDAC) remains elusive. In this study, we revealed the essential role of miR-485-3p in PDAC, particularly its impact on cancer stemness and gemcitabine resistance under hypoxic conditions. We found substantial downregulation of miR-485-3p in PDAC tissues, with lower expression correlating to poor patient outcomes. Mechanistically, miR-485-3p influenced stemness characteristics, as evidenced by reduced tumor-sphere formation and increased sensitivity to gemcitabine upon overexpression. Moreover, we identified SOX9 and SLC7A11 as two targets of miR-485-3p, which play a vital role in stemness and ferroptosis. Under the hypoxic condition, DNMT3B expression was upregulated, leading to hypermethylation of the miR-485-3p promoter region. The reduced miR-485-3p expression promoted stemness and chemoresistance of PDAC. In conclusion, our findings elucidate the intricate interplay of hypoxia, epigenetic modifications, and ferroptosis in PDAC and shed light on potential avenues for targeted interventions that modulate cancer stemness and chemosensitivity, offering prospects for improved therapeutic strategies for PDAC.